Research Progress of Drug Prophylaxis for Lens Capsule Opacification after Cataract Surgery - Rong-Pei Zhang; Zheng-Gao Xie (Journal of Ophthalmology)
Phacoemulsification combined with intraocular lens (IOL) implantation is the international standard operation procedure for cataract and has been generalized worldwide. However, lens capsule opacification, one of the common complications after cataract surgery, impacts the recovery of patients’ visual function to a large extent. Lens capsule opacification has two types, anterior capsule opacification (ACO) and posterior capsule opacification (PCO), according to the location. There is not an accepted approach to treat ACO. Nd : YAG laser capsulotomy, the common treatment of PCO, can effectively improve the vision, but may cause a series of complications and is inappropriate for children who are too young to cooperate with this treatment. It is generally known that the responses of lens epithelial cells (LECs) after cataract surgery, including cell proliferation, migration, and epithelial-mesenchymal transition (EMT), play a key role in the pathogenesis of lens capsule opacification. Scholars found that substantial drugs can reduce the occurrence of lens capsule opacification by inhibiting, clearing, or killing LECs, and made great efforts as well as innovations on the exploration of drug species or modes of administration. This article is a systematic interpretation and elaboration about how to prevent lens capsule opacification after cataract surgery via different drugs.